Tingkat Konsumsi Energi, Durasi Penggunaan Gawai, dan Status Gizi Anak Sekolah Dasar - Tania Putri Cahyani, I Gusti Ayu Agung; Suiraoka, I Putu; Kusumajaya, Anak Agung Ngurah (Jurnal Kesehatan, 2023)
Nutritional status is influenced by the level of food consumption, especially energy. Nutritional status is indirectly affected by the use of gadgets. This study aims to determine the relationship between the level of energy consumption and duration of use of gadgets with the nutritional status of elementary school children in Mengwi. This type of research is an observational study with a cross-sectional design and uses 83 samples with ages of 9-11 years. The data was collected using the 24-hour recall method and questionnaire. The data was presented with a frequency table and then analyzed using Pearson. The results showed that the average energy consumption level of the sample was 103%, and the average duration of the sample's use of gadgets was 4 hours 25 minutes; 16.9% of the samples with overweight nutritional status and 9.6 with obesity nutritional status had consumption levels above the requirement, 7.2% had more nutritional status, and obesity had an excessive gadget use duration. The results of the Pearson show a relationship between the level of energy consumption and nutritional status with value (p-value=0.00), and there is no relationship between the duration of use of gadgets with nutritional status with value (p-value=0.53). There is a significant relationship between the level of energy consumption and the nutritional status of elementary school students in the Mengwi District. It is expected that elementary school students in Mengwi District will be able to pay attention to nutritional intake, especially energy consumption, and increase their physical activity.